2018
DOI: 10.3168/jds.2017-13720
|View full text |Cite
|
Sign up to set email alerts
|

Plane of nutrition before and after 6 months of age in Holstein-Friesian bulls: II. Effects on metabolic and reproductive endocrinology and identification of physiological markers of puberty and sexual maturation

Abstract: The aim of this study was (1) to examine the effect of plane of nutrition during the first and second 6 mo of life on systemic concentrations of reproductive hormones and metabolites in Holstein-Friesian dairy bulls, and (2) to establish relationships with age at puberty and postpubertal semen production potential. Holstein-Friesian bull calves (n = 83) with a mean (standard deviation) age and body weight of 17 (4.4) d and 52 (6.2) kg, respectively, were assigned to a high or low plane of nutrition for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 50 publications
5
26
0
Order By: Relevance
“…However, Lo-Hi bulls did not become fatter or have a greater muscle depth than bulls that were on a Hi diet pre-6 mo of age, highlighting the limited compensability of muscle and fat deposition in Holstein-Friesian bulls. Bulls on the Hi diet pre-6 mo had greater subcutaneous fat than Lo bulls at 6 mo, in line with the experimental design, suggesting that Hi bulls would have had greater fat and thus energy reserves when it is most important (early life), possibly leading to increased systemic concentrations of leptin (Byrne et al, 2018) which have been Values within row with different superscripts differ significantly.…”
Section: Discussionsupporting
confidence: 66%
“…However, Lo-Hi bulls did not become fatter or have a greater muscle depth than bulls that were on a Hi diet pre-6 mo of age, highlighting the limited compensability of muscle and fat deposition in Holstein-Friesian bulls. Bulls on the Hi diet pre-6 mo had greater subcutaneous fat than Lo bulls at 6 mo, in line with the experimental design, suggesting that Hi bulls would have had greater fat and thus energy reserves when it is most important (early life), possibly leading to increased systemic concentrations of leptin (Byrne et al, 2018) which have been Values within row with different superscripts differ significantly.…”
Section: Discussionsupporting
confidence: 66%
“…The animal model and management has previously been described by Byrne et al . 18 . Briefly, twenty Holstein-Friesian bull calves with a mean (±S.D.)…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected on a fortnightly basis to determine systemic concentrations of LH and was quantified by RIA as previously described by Byrne et al . 18 . Death was confirmed by exsanguination followed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…The advent of genomic selection in the dairy industry has resulted in the identification of sires for use in artificial insemination within weeks of birth and semen from these young bulls is in high demand once they reach puberty. Studies have shown that plane of nutrition in early calf-hood plays a critical role in the timing of the onset of puberty in bulls [ 1 3 ]. Recently, our research group has demonstrated that a high plane of nutrition prior to, but not after 6 months of age can accelerate puberty in Holstein-Friesian bulls by approximately 1 month [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that plane of nutrition in early calf-hood plays a critical role in the timing of the onset of puberty in bulls [ 1 3 ]. Recently, our research group has demonstrated that a high plane of nutrition prior to, but not after 6 months of age can accelerate puberty in Holstein-Friesian bulls by approximately 1 month [ 3 ]. This has been associated with the advancement of a transient rise in systemic concentrations of luteinising hormone (LH), which normally occurs between approximately 8 and 20 weeks of age [ 4 ].…”
Section: Introductionmentioning
confidence: 99%